TINGKAT PENGARUH PEMASARAN DALAM MELAKSANAKAN “RESTAURANT BLACK CANYON COFFEE” - Hilda Pradina; Mailatul muyassaroh (Manivest : Jurnal Manajemen, Ekonomi, Kewirausahaan, dan Investasi, 2023)
Marketers must not only be able to sell their products or services, but also must learn what the needs and wants of consumers are now and in the future and know how to present the best alternatives to consumers who are the main target, so that marketers can market and customize their products. become superior to its competitors. After knowing the situation and conditions of increasingly fierce competition between companies where companies still want how to retain their customers so as not to decline, company leaders are also expected to be quick to respond to changes that occur around them.